(untitled) (American Journal of Islam and Society, 1995)
An extensive corpus of literature on the phenomenon of the Islamic movement as a reaction to modernization and modernity has appeared during the past two decades. In this important category of research, Islamic discourse and its sociopolitical impact may be explained in tenns of the growing sense of alienation and exclusion generated by the changes of modem times. As a result, a dichotomous model of analysis has been widely employed in many of the recent approaches to Islam and Muslims, a model that pits the "modem," "progressive," and "rational" against the "traditional," "reactionary," and "emotional." In contrast, only a few attempts have been made to understand contemporary Islamic discourse(s) and movements as the quintessential products of the modernization process in the Muslim world. The case for this alternative, though complementary, approach can be formulated on the basis of a sociocultural analysis of the views and backgrounds of modem lslamists. For more than thirteen centuries of its history, Islam was defined intellectually and practically by the ulama class. This vital and pervasive social force, although open and accessible to various sections of society, was not without its own boundaries in the areas of culture, education, or piety. Progressively, of course, and for reasons that cannot be dealt with here, the ulama class was transformed into an established social institution and preserved by families with long scholarly traditions and a complex network of a particular kind of power. Twentieth-century Islamists are, by and large, graduates of modem (western?) schools who have received intensive training in modem disciplines and methodologies. Their breeding milieu, in most cases, are modem urban centers in the Muslim world and modem social classes. Thus they have little to do with the ancient institution of the ulama. In fact, their advent has marked an era of decline for the ulama class. Traditional Islam, or that of the ulama, has been and will always be a strong tributary to contemporary Islamic thought and its world vision. But the latter’s idioms, logic, symbols, structural relations, inner dynamics, and ultimate goals are necessarily of modem geneaology. In this issue of AJISS, A. I. Tayob presents a brilliant study on the "Paradigm of Knowledge of the Modem Islamic Resurgence." Grounding his analysis on Foucault’s themes of power relations between disciplines, ...